First case of vaccine-strain varicella infection as manifestation of HIV in healthcare worker: a case report and review of the literature. Issue 4 (December 2017) - Navalkele, B.D.; Henig, O.; Fairfax, M.; Flanagan, E.; Upfal, M.; Russell, J.; Dhar, S.; Kaye, K.; Chopra, T.
Summary: Live-attenuated varicella vaccination is safe in non-immunocompromised populations and is associated with rare non-serious adverse events. A healthcare worker (HCW) developed varicella infection, and exposure investigation led to immunization against varicella in an exposed non-immune HCW. Subsequently, vaccine-strain-induced disseminated varicella and progressive outer retinal necrosis in the exposed HCW resulted in identification of undiagnosed human immunodeficiency virus infection. This article reviews serious adverse events from varicella vaccination, and extreme caution is advised prior to live vaccination of HCWs.